Pathways of atopic disease and neurodevelopmental impairment: assessing the evidence for infant antibiotics. (2nd September 2022) - Volker, Elizabeth; Tessier, Carmen; Rodriguez, Nicole; Yager, Jerome; Kozyrskyj, Anita
ABSTRACT: Introduction: Epidemiologic studies are starting to report associations between antibiotic use in early life and neurodevelopmental disorders. Through mechanisms within the gut microbiota-brain axis, indeed, it is plausible that infant antibiotic treatment plays a role in the development of atopic disease and neurodevelopmental disorders. Areas covered: This narrative review summarizes and interprets published evidence on infant antibiotic use in future outcomes of atopic disease, and neurodevelopmental delay and disorders, including attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD). To this end, we critically assess study bias from two main confounding factors, maternal/infant infection and infant feeding status. We also discuss common mechanisms that link atopy and neurodevelopment, and propose hypotheses related to immune activation and the gut microbiome. Expert opinion: Atopic disease and neurodevelopmental disorders share many risk factors and biological pathways. Infant antibiotic use has been linked to both disorders and is likely a marker for prenatal or infant infection. The mediating role of breastfeeding can also not be discounted. The exploration of causal pathways along the gut-brain axis leading toward neurodevelopmental impairment is evolving and of future interest.